2022
DOI: 10.1097/ccm.0000000000005436
|View full text |Cite
|
Sign up to set email alerts
|

Use of Extracorporeal Membrane Oxygenation in Acutely Poisoned Pediatric Patients in United States: A Retrospective Analysis of the Extracorporeal Life Support Registry From 2003 to 2019

Abstract: OBJECTIVES: To describe the use of extracorporeal membrane oxygenation (ECMO) in the management of pediatric poisoning in the United States and to identify predictors of mortality. DESIGN: Retrospective cohort study. SETTING: Data reported to the Extracorporeal Life Support Organization by 76 U.S. ECMO centers from 2003 to 2019. PATIENTS: Pediatric patients (0–18 yr) receiving ECMO for poisoning. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: During our study period, 86 cases of acute poisoning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Interventions frequently performed to treat antidepressant drug toxicity include administering substances to prevent or reduce absorption of the toxic substance through the GI tract, giving an antidote (if available), sodium bicarbonate administration for alkalization, ILE therapy, and extracorporeal supportive treatments 19,20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions frequently performed to treat antidepressant drug toxicity include administering substances to prevent or reduce absorption of the toxic substance through the GI tract, giving an antidote (if available), sodium bicarbonate administration for alkalization, ILE therapy, and extracorporeal supportive treatments 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…6 Interventions frequently performed to treat antidepressant drug toxicity include administering substances to prevent or reduce absorption of the toxic substance through the GI tract, giving an antidote (if available), sodium bicarbonate administration for alkalization, ILE therapy, and extracorporeal supportive treatments. 19,20 One of the treatments used in OG antidepressant poisoning is intravenous sodium bicarbonate therapy. Plasma alkalization is another commonly used method in antidepressant poisoning, especially in patients with signs of severe cardiovascular and neurological toxicity due to TCAs.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, the articulation of ECMO rescue teams to bring therapies to patients too unstable to travel has expanded access to life-saving therapy by both ground and air ambulance modalities (155). ECMO survival rates have increased, with survival for adult pulmonary ECLS 66%, adult cardiac ECLS 59%, and ECPR 41% from the April 2022 ELSO Registry Report; pediatric and neonatal ECLS survival rates are even higher including when used to help manage pediatric poisoning or stem cell transplantation (156)(157)(158). The number of ECMO centers has also increased significantly from 150 in 2008 to over 500 in 2022, paralleling the increase in indications, as well as dwindling contraindications for ECLS approaches including as a bridge to Left Ventricular Assist Device placement for cardiogenic shock management or pulmonary embolism rescue (159)(160)(161).…”
Section: Extracorporeal Techniquesmentioning
confidence: 99%
“…Di Nardo et al observed that 86 acutely poisoned pediatric patients were rescued with ECMO in the USA from 2003 to 2019. 28 The use of ECMO in these patients progressively increased over time, reflecting the overall increased use of ECMO for diverse medical indications. Hydrocarbons, chemical asphyxiants, neuroactive agents, opioid/analgesics, and cardiovascular agents were the most frequently reported exposures requiring ECMO.…”
Section: Ecmo Support For Poisoned Pediatric Patientsmentioning
confidence: 99%